The Influence of Principal Managerial Competence and Teacher Welfare on Teacher Work Motivation in Elementary Schools of Belang District - Languju, Marlon Novis; Wullur, Mozes M.; Usoh, Elni Jeini; Mongdong, Romi J. (International Journal of Information Technology and Education, 2026)
Teacher work motivation is a critical determinant of instructional quality in elementary schools, yet it remains susceptible to organizational and socioeconomic pressures, particularly in rural educational settings in Indonesia. Preliminary observations in the Belang District revealed persistent motivational challenges, including suboptimal punctuality, limited pedagogical innovation, and teachers’ economic necessity to seek supplementary employment. This study aims to examine the influence of principal managerial competence and teacher welfare, both independently and simultaneously, on teacher work motivation in the elementary schools of Belang District. A quantitative ex-post facto survey design was employed, involving 106 active teachers as the main sample and 27 try-out respondents selected via Proportional Random Sampling from a population of 106 teachers across 12 elementary schools; data were collected using a validated Likert-scale questionnaire and analyzed through multiple linear regression with classical assumption testing. Principal managerial competence significantly and positively predicted teacher work motivation (t = 4.683; p = 0.000), and teacher welfare likewise demonstrated a significant positive partial effect (t = 3.892; p = 0.001). Simultaneously, both variables jointly explained a substantial proportion of variance in teacher work motivation (F = 33.599; p = 0.000; R2 = 0.985), yielding the regression equation Y = 52.792 + 0.085X1 + 0.025X2. Managerial competence exhibited a relatively stronger predictive coefficient, indicating a dominant role in driving motivational outcomes compared to welfare. These findings confirm that effective principal managerial leadership and adequate teacher welfare are complementary and statistically robust predictors of teacher work motivation in rural Indonesian elementary schools. The practical implication is that district education authorities should prioritize concurrent investment in principals’ managerial capacity development and structural welfare equity for teachers, particularly those with honorary employment status, as integrated policy interventions.